A aplicação de uma sequencia didática: caixa eletrônico - Kochhann, Maria Elizabete Rambo; Carvalho, Lizete Maria Orquiza de [UNESP]; Lopes Júnior, Jair [UNESP] (My University, 2012)
This paper aims at analyzing the initial actions of a project called Education Observatory with Focus on Mathematics and Science Initiation, which involves three Brazilian universities and proposes interventions in school units with research-action methodology. The main result is that the pillar of the project is a network of specific actions with students of basic education, which seek to put in evidence the possibilities of teaching/learning Mathematics by making use of different methodological proposals such as interactive activities, math games, problem solving situations, in few words, activities that may be distinguished by the participation of students and by helping them to understand the content of Mathematics. Such actions, we hope, will contribute to teacher education and may occur in concomitance with educational problems faced by University-School partnerships.

Este trabalho pretende analisar as ações iniciais de um projeto chamado “Observatório da Educação com Foco em Matemática e Iniciação em Ciências”, o qual envolve três universidades brasileiras e se propõe realizar intervenções em unidades escolares com a investigação-ação como metodologia. O principal resultado é o de que o pilar do projeto se constitui em uma rede de ações pontuais de intervenção com alunos da Educação Básica, as quais pretendem evidenciar as possibilidades de ensinar/aprender Matemática fazendo uso de diferentes abordagens metodológicas tais como atividades interativas, jogos matemáticos, resolução de situações-problema, enfim, que primem pela participação dos estudantes e os levem a compreender a matemática presente nessas situações. Tais iniciativas, esperamos, irão contribuir para que a formação inicial de professores ocorra em concomitância com o enfrentamento de problemas educacionais encontrados pela parceria universidade-escola.
Implementation of a didactic sequence: the automated teller machine
Keywords: Education center; Initial formation; Instructional sequences; Observatório da educação; Formação inicial; Sequências didáticas